Determinan kejadian malaria menggunakan rapid diagnostic test (RDT) pada wilayah endemis Puskesmas Mahu - Denisius Umbu Pati; Aris Umbu Hina Pari (Holistik Jurnal Kesehatan, 2024)
Background: Malaria is an infectious disease that is still a serious health problem in endemic areas, including in the Mahu Health Center area, East Sumba Regency. The disease is caused by protozoa of the genus Plasmodium and is transmitted through the bite of female Anopheles mosquitoes. Malaria control is an important part of efforts to achieve the 2030 Sustainable Development Goals (SDGs). However, environmental factors and community behavior in endemic areas often increase the risk of transmission. Purpose: To analyze the determination of malaria incidence using Rapid Diagnostic Test (RDT). Method: Analytical observational study with a cross-sectional approach and 310 respondents were selected through a multistage random sampling technique. Data collection was carried out through direct observation, structured interviews, and documentation, then analyzed using a linear regression test. Results: The distance between the house and the breeding place, the presence of livestock pens, the availability of ventilation nets, the use of nets while sleeping, and the use of mosquito repellent significantly influenced the incidence of malaria with a p value <0.05. Conclusion: Environmental factors and community behavior such as the distance of the house from mosquito breeding sites, the presence of livestock pens, the availability of mosquito nets, the use of mosquito nets, and the use of mosquito repellent are determining factors for malaria incidence in endemic areas. Suggestion: Environmental interventions such as rearranging the location of mosquito breeding sites and livestock pens, as well as providing education to the community about the importance of using mosquito nets and mosquito repellent as preventive measures, need to be improved.   Keywords: Endemic; Malaria; Rapid Diagnostic Tests (RDT).   Pendahuluan: Malaria merupakan penyakit menular yang masih menjadi masalah kesehatan serius di daerah endemis, termasuk di wilayah Puskesmas Mahu, Kabupaten Sumba Timur. Penyakit ini disebabkan oleh protozoa genus Plasmodium dan ditularkan melalui gigitan nyamuk Anopheles betina. Pengendalian malaria menjadi bagian penting dari upaya mencapai Sustainable Development Goals (SDGs) 2030. Namun, faktor lingkungan dan perilaku masyarakat di daerah endemis seringkali meningkatkan risiko penularan. Tujuan: Untuk menganalisis determinan kejadian malaria menggunakan Rapid Diagnostic Test (RDT). Metode: Penelitian observasional analitik dengan pendekatan cross-sectional dan sebanyak 310 responden dipilih melalui teknik multistage random sampling. Data dikumpulkan melalui observasi langsung, wawancara terstruktur, dan dokumentasi, kemudian dianalisis menggunakan uji regresi linear. Hasil: Jarak rumah dengan breeding place, keberadaan kandang ternak, ketersediaan kasa ventilasi, penggunaan kelambu saat tidur, dan penggunaan obat nyamuk secara signifikan memengaruhi kejadian malaria dengan perolehan p-value < 0.05. Simpulan: Faktor-faktor lingkungan dan perilaku masyarakat, seperti jarak rumah dengan breeding place, keberadaan kandang ternak, ketersediaan kasa ventilasi, penggunaan kelambu, dan penggunaan obat nyamuk, merupakan determinan penting dalam kejadian malaria di daerah endemis. Saran: Harus adanya peningkatan intervensi lingkungan, seperti penataan ulang lokasi breeding place dan kandang ternak, serta edukasi masyarakat tentang pentingnya penggunaan kelambu dan obat nyamuk sebagai upaya pencegahan.   Kata Kunci: Endemis; Malaria; Rapid Diagnostic Test (RDT).